Ecological indices of key biological groups in Southern Iraqi marshland during 2005-2007 - Hussain, N.A.; Ali, A.H.; Lazem, L.F. (Mesopotamian Journal of Marine Sciences, 2022)
Yearly values of ecological indices were calculated for several key biological groups include macrophytes, macroinvertbrates, fishes and waterfowls during the period 2005-2007 in Huwaiza, West Hammar and East Hammar marshes in Southern Iraq. Ecological indices increase for the studied key biological groups in 2006 in the three monitored marshes in comparison with that of 2005. Ecological indices of macrophytes and waterfowls assemblages increase steadly from 2005 towards 2007. On the contrary macroinvertebrates and fishes suffer severe decline in 2007 mainly due to reduced water level. Continuous improvement in ecological indices of macrophytes and waterfowls in two of the restored marshes indicated that reduced water level was less harsh to them than to the other two groups. In spite of the slow recovery in ecological indices in the monitored marshes, diversity and richness values fluctuated between poor to moderate status and semi-integrated to disturbed, respectively. Cases of poor status and disturbed were more common and limited good ones were noticed. Most evenness values indicated absence of dominance cases, except two below the acceptable limit (0.5) were scored both were during 2007. What is clear is that the yearly hydrological period plays a major role in manipulating the biodiversity and repercussion ecological indices in the Southern restored marshes. Lower values of ecological indices indicated that the environment of Southern marshes still disturbed and need more time and care to be fully restored.